FAKTOR-FAKTOR YANG MEMPENGARUHI KETIMPANGAN DISTRIBUSI PENDAPATAN RUMAH TANGGA DI KABUPATEN MINAHASA - Tesalonika Chrisdiantien Dondo; Noortje Marsellanie Benu; Elsje Pauline Manginsela (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2019)
The objective of research is to find out and analyze what factors influence the inequality of income distribution in Minahasa District. The study was conducted from April 2018 to January 2019. The data used in this study were secondary data during the period 2003 to 2017. Secondary data in this study were obtained from the Minahasa Regency Central Bureau of Statistics Agency and North Sulawesi Provincial Statistics Agency Agencies such as the Index Gini as one of the measures most often used to measure the level of overall income inequality, economic growth in 2003-2017, the number of poor people from 2003-2017, and the human development index for 2003-2017. The results showed that economic growth and the number of poor people in Minahasa District significantly affected the inequality of income distribution in Minahasa District. Whereas the human development index variable has no significant effect.Keywords: Inequality In Income Distribution, Household